Die Anwendung von Digitalrechnern zur Steuerung und Datenverarbeitung im spektroskopischen Laboratorium - Richard R. Ernst (CHIMIA)
A survey is given over the different possibilities and needs for computer applications in chemical spectroscopy. Four different phases in the spectroscopic data gathering process are distinguished: (1) the spectroscopic experiment, (2) data transformation and filtering procedure, (3) the data reduction process and (4) the data interpretation. It is shown that in all four phases computers may enhance performance and efficiency. Particularly, Fourier transform techniques which depend on the availability of digital computers have opened new dimensions to spectroscopy.